77.2k views
2 votes
Simplify: 2y + x + 3x - y

1 Answer

7 votes

Answer:

y + 4x

Explanation:

For this problem, we will simply combine like terms using the distributive property and the commutative property.

First, let's use the commutative property:

2y + x + 3x - y

= 2y - y + x + 3x

Second, let's use the distributive property:

2y - y + x + 3x

= y ( 2 - 1 ) + x ( 1 + 3 )

= y ( 1 ) + x ( 4 )

= y + 4x

Hence, the simplification of 2y + x + 3x - y is y + 4x.

Cheers.

User ElBel
by
5.7k points